EKSPLORASI ETNOMATEMATIKA PADA MOTIF BATIK NAGORI KUANTAN SINGINGI - Dwi Miftahurrahmi Putri; Juandini Juandini; Jesi Alexander Alim (Universitas Muhammadiyah Makassar, 2022)
This research is motivated by the aim of varying the teaching that is too formal and theoretical which affects students' interest in learning mathematics. Therefore, learning mathematics is needed at the beginning of formal mathematics education, uniting mathematics and culture in certain activity phases according to the level of student development. The presence of culturally nuanced mathematics makes an important contribution to school mathematics. This study focuses on one of the cultural objects in Kuantan Singingi district, namely Batik Nagori. The purpose of this study is to determine the mathematical concepts of geometry contained in batik motifs. This study uses a qualitative research type with an ethnographic approach. The data collection method used is literature study. In analyzing the data using data reduction, data presentation, drawing conclusions and verification. The results of this study indicate that there are mathematical concepts of geometry in the form of triangles, hexagons, squares, trapezoids.